N-Soliton Solutions of the Nonisospectral Generalized Sawada-Kotera Equation - Jian Zhou; Xiang-Gui Li; Deng-Shan Wang (Advances in Mathematical Physics)
The soliton interaction is investigated based on solving the nonisospectral generalized Sawada-Kotera (GSK) equation. By using Hirota method, the analytic one-, two-, three-, and N-soliton solutions of this model are obtained. According to those solutions, the relevant properties and features of line-soliton and bright-soliton are illustrated. The results of this paper will be useful to the study of soliton resonance in the inhomogeneous media.